Diet-Dependent and Diet-Independent Hemorheological Alterations in Celiac Disease: A Case-Control Study. Issue 11 (12th November 2020) - Szakács, Zsolt; Csiszár, Beáta; Nagy, Mátyás; Farkas, Nelli; Kenyeres, Péter; Erős, Adrienn; Hussain, Alizadeh; Márta, Katalin; Szentesi, Andrea; Tőkés-Füzesi, Margit; Berki, Tímea; Vincze, Áron; et al.
Abstract : INTRODUCTION: Hemorheology is the study of the flow properties of the blood and its elements, which, together with natural anticoagulants, are important determinants of cardiovascular events. This study aimed to assess hemorheological and natural anticoagulant profiles of patients with celiac disease (CeD) comprehensively. METHODS: Our study is a case-control study (registered under ISRCTN49677481) comparing patients with CeD with age- and sex-matched control subjects (1:1). We measured erythrocyte deformability (ED) at high (3–30 Pa) and low shears (0.3–3 Pa), erythrocyte aggregation, whole blood viscosity, plasma viscosity, and natural anticoagulants (protein C, protein S, and antithrombin activity). Adherence to gluten-free diet was estimated through dietary interview and urine gluten immunogenic peptide (urine GIP) detection. RESULTS: After matching, we analyzed the data of 100 study participants. ED at high shears was impaired in CeD ( P < 0.05 for all shears, confirmed by random forest analysis) independently of findings on CeD-specific serological assessment and urine GIP detection but slightly dependently on dietary adherence ( P = 0.025 for 30 Pa shear). ED at low shears seemed to be impaired only in urine GIP+ CeD patients ( P < 0.05 for all comparisons with urine GIP− CeD patients and control subjects). All parameters describing erythrocyte aggregation and whole blood viscosity were shifted toward a prothrombotic direction in patients with CeD with poor dietary adherence compared with those with good dietary adherence. Plasma viscosity and activity of natural anticoagulants did not differ across groups. DISCUSSION: We observed diet-dependent and diet-independent prothrombotic hemorheological alterations in CeD, which can contribute to the elevated cardiovascular risk. The untoward metabolic changes during gluten-free diet, which can further aggravate hemorheological status, may indicate the implementation of prevention strategies.